PENGEMBANGAN APLIKASI CERITA RAKYAT JAKA POLENG BERBASIS CULTURALLY RESPONSIVE TEACHING UNTUK MENINGKATKAN KOMPETENSI MENULIS REKON SISWA KELAS II SD NEGERI JAGALEMPENI 01, KABUPATEN BREBES - Nugroho, Dani; Suyitno; Wakhyudin, Husni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low competence of writing essays of grade II students of SD Negeri Jagalempeni 01, Brebes Regency. Students still have difficulty understanding the storyline and rewriting events in sequence. In addition, learning is still dominated by teachers and the use of digital media in learning Indonesian is still limited. This study aims to describe the development process, determine the level of validity and feasibility, and analyze the improvement of rekon writing competence through the Jaka Poleng folklore application based on Culturally Responsive Teaching (CRT). This research uses the Research and Development (R&D) method with the ADDIE model which includes the Analysis, Design, Development, Implementation, and Evaluation stages. The field trial was carried out on 20 students in grade II of SD Negeri Jagalempeni 01. Data was collected through observation, interviews, documentation, validation questionnaires and user responses, as well as pretest and posttest tests. Data analysis used qualitative and quantitative descriptive techniques with percentage calculation and N-Gain test. The results of the study show that the CRT-based Jaka Poleng folklore application was successfully developed through the ADDIE model. The validity rate obtained a percentage of 97.5% from media experts and 98.75% with the very valid category. The eligibility level obtained a percentage of 100% from teachers and 93% from students with the very feasible category. The results of the N-Gain test obtained a score of 0.9294 with a high category and an N-Gain Percent of 92.944% which shows an increase in the competence of writing a recon in the high category. Thus, the application developed is very valid, very feasible, and able to improve the competence of writing essays for grade II students of SD Negeri Jagalempeni 01.